Dissolved neodymium and hafnium isotopes and rare earth element data of near-bottom water samples from RV Meteor cruise M147 - Antao Xu; Ed C Hathorne; Florian Scholz; Ling Chen; Andrea Koschinsky; Martin Frank (PANGAEA, 2025)
The dataset comprises isotope compositions of dissolved neodymium (Nd) and hafnium (Hf), together with particulate Nd and Hf isotope data from surface estuarine sediments. It further includes concentrations of rare earth elements and yttrium (REY) as well as dissolved hafnium ([Hf]) in near-bottom waters and surface sediments collected across the Amazon shelf and slope. All samples were obtained during RV Meteor cruise M147 (April–May 2018), conducted as the official process study GAPR11 within the framework of the international GEOTRACES program.